Impact of stabilizing methods on the in vitro protein digestibility of Ulva fenestrata - Helgesson, Klara (My University, 2024)
The seaweed Ulva fenestrata has gained interest from a dietary perspective due to its promising protein content, well-balanced amino acid composition and high levels of vitamin B12. It is however highly perishable and needs to be stabilized quickly after harvesting. Rinsing is often employed before stabilizing. Existing studies have reported a low or moderate digestibility for crude seaweed proteins, but there is a lack of studies exploring how the digestibility U. fenestrata proteins is affected by stabilizing methods. Time and temperature are two critical factors decisive for whether the digestibility is improved or impaired during processing. In this thesis, the effect of a selection of stabilizing methods on the in vitro protein digestibility of U. fenestrata was studied. A modified INFOGEST 2.0 static in vitro digestibility protocol was used, including casein as a reference. It was concluded that the chosen stabilizing methods did not alter the protein digestibility, and can be used without compromising the nutritional quality of the seaweed proteins. Future prospects and method improvements were discussed.
Keywords: Ulva fenestrata; static in vitro digestion; INFOGEST 2.0; protein; degree of hydrolysis